Risk Factors for Developing Rheumatoid Arthritis in Patients With Undifferentiated Arthritis and Inflammatory Arthralgia - Novella-Navarro, Marta; Plasencia-Rodríguez, Chamaida; Nuño, Laura; Balsa, Alejandro (Frontiers in Medicine, 2021)
Currently, there is an increasing interest in treating individuals at risk of rheumatoid arthritis (RA) to prevent the development of this chronic condition. In this sense, research has focused attention on the early identification of predictive factors of this disease. Autoantibodies and markers of systemic inflammation can be present long before clinical arthritis and maturation of the immune response seems to coincide with RA development. The phase of inflammatory arthralgia preceding clinical arthritis is likely to be an important part of the window of opportunity and, starting treatment might prevent progression to chronic arthritis. Additionally, the early diagnosis and treatment initiation, in patients with inflammatory arthritis at risk of persistence and/or erosive progression, are fundamental because may allow optimal clinical responses, better chances of achieving sustained remission, preventing irreversible organ damage and optimizing long-term outcomes. This review aims to give an overview of clinical risk factors for developing RA, both in suspected arthralgia and in undifferentiated arthritis. Besides taking into consideration the role of serological markers (immunological and acute phase reactants) and clinical features assessed at consultation such as: articular affection and patient´s clinical perception. Other features as sociodemographic and environmental factors (lifestyle habits, microbiota, periodontal disease among others), have been included in this revision to give an insight on strategies to prevent development of RA and/or to treat it in early stages.